Spectroscopic Studies of 5-o-Tolyl-2-pentene Adsorbed on 5A, NaY and NaX Zeolites - BARDAKCI, BELGiN (Asian Journal of Chemistry, 2010)
The adsorption of 5-o-tolyl-2-pentene in liquid phase on 5A, NaY and NaX zeolites has been studied by IR spectroscopy. The slightly higher preference of Na cation-exchanged zeolites for an alkene can be clarified in term of stronger interaction of unsaturated hydrocarbons with ionic nature of the zeolite surface. The IR results show that methyl and methylene groups are the sources of adsorption on cationic site of the zeolites.